High intensity short duration soccer fatigue simulation reduced hamstring eccentric strength in Elite U19 players / Mohamad Azraie Mohd Faozi and Raja Mohammed Firhad Raja Azidin - Mohd Faozi, Mohamad Azraie; Raja Azidin, Raja Mohammed Firhad (Universiti Teknologi MARA, 2023)
Previous studies found most soccer injuries occur during the latter stage of match-play suggesting fatigue as an important factor contributing to injuries. The purpose of this study is to investigate the effects of a high intensity, short duration soccer-specific fatigue simulation on hamstring eccentric strength among elite U19 soccer players. Twelve (n=12; age 18.3 ± 0.5 years; weight 62.3 ± 6.4 kg; height 171 ± 6.6 cm) elite U19 soccer players completed a soccer-specific fatigue simulation (SFS5) and isokinetic dynamometer protocol. Before exercise (time 0 min), immediately after SFS5 (time 5 min) and after 15 mins SFS5 (time 15 min), participants performed three maximal dominant limbs at 120°s-1 for eccentric hamstring muscle actions. A one-way repeated measures ANOVA was used to identify significant differences between conditions and over time, with α=0.05. A significant time dependent reduction in hamstring eccentric at time 5 min (9.5%) and time 20 min (9.7%) was observed. These findings suggest eccentric training during fatigue state should be a primary consideration in injury prevention program. Our findings also recommended the inclusion of a short duration, high intensity soccer-specific fatigue simulation as part of pre-season hamstring strain injury risk screening and return to play assessment to ensure the effectiveness in identifying the markers of hamstring strain injury risk in soccer players.